ECLECTICS, FUSION AND KITCH IN THE DESIGN OF RESTAURANT INTERIORS - Габрель, Т. М. (Art and Design, 2020)
Outline and articulate the specifics of each of the listed interior styles. Create the ability to correctly set the interior to the style specified by matching the dominant characteristic. The method of field surveys of public institutions of the city of Lviv and general scientific methods were used. Literature sources on the topic of the study are considered in accordance with the methods of comparative analysis. The systematization of the material is based on the techniques of analysis, synthesis and analogies as well. Based on the literature review of approaches to the classification of interiors in considered styles have been identified; the lack of uniform interpretation of their features was established. At the same time, the existence of a peculiar identity of their perception in the scientific literature was confirmed. Samples of modern interiors of Lviv restaurants are considered and their style is demonstrated. The concept of the existence of a key characteristic for each of the styles is substantiated, which allows them to better determine their belonging to a particular style, in particular: fusion - a blend of modern and antique; eclecticism - a mixture of interior elements of historical styles without the use of modern elements; kitsch - an imitation of the essence of space and lack of environmental approach. It is to determine the dominant characteristic for attributing the interior to one of these styles. For greater efficiency, the focus is on the formation of one dominant trait, rather than a complex system of indicators and characteristics. The author’s dominant attributes make it possible to classify the interior style more efficiently, which leads to better communication between the designer and the customer, and promotes better understanding in the environment of the professional community of interior designers.